The Effect of Financial Knowledge and Income on Pension Fund Planning Behavior with Locus of Control as A Mediation Variable - Alien Nuril Wardani; Mellyza Silvy (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
This study aims to examine the influence of financial knowledge and income on retirement planning behavior with locus of control as a mediation variable. The study included 321 respondents who met criteria such as having a total family income of at least IDR 4.000.000 per month, having worked for at least 2 years, living in Surabaya, Gresik, or Sidoarjo, and having financial management responsibilities in the family. The data analysis technique uses Partial Least Squares Structural Equation Modeling (PLS-SEM) with PLS 6.0. This study finds that financial knowledge and income positively influence retirement planning behavior, and that locus of control can mediate their effects.